Monitoring the Degradation of 4-Sulfonyldipenyl-Pyromellitic Dianhy-dride-Based Polyamic Acid by Trametes Versicolor - Yazgan, İdris (Celal Bayar University Journal of Science, 2019)
Polyamic acid (PAA) polymers have been utilized over 60 years in industry as precursors of polyimide, and currently direct utilization of PAA polymers have got great attention for material science applications. Mass utilization of synthetic polymers pose threat to living organisms and nature, so their effective degradation is important. In this study, for the first time, degradation of 4-sulfonyldipenyl-pyromellitic dianhydride based PAA (DSPAA) polymers were performed in batch bioreactor system. 1H COSY NMR was utilized to enlight the possible mechanism behind Tramates versicolor mediated degradation of DSPAA polymer. Elimination of aromatic peaks belong to DSPAA polymer and its amine monomer were monitored to evaluate the degradation while formation of new peaks was taken into account to propose possible degradation pathway. NMR studies revealed that 20-day incubation in the designed media is enough to totally eliminate 1 mg/mL DSPAA. The findings can contribute to the knowledge of fungi mediated aromatic polymer degradation, which is accepted a promising way to eliminate polymer pollution
Keywords: Engineering; Biodegradation; Bioreactor; NMR; Polyamic acid; Trametes versicolor; Mühendislik